APLIKASI PENDATAAN ASET PADA UPT. PENGUSAHAAN ASET ACEH PT. KERETA API INDONESIA (PERSERO) - Rusmini, Rusmini (KITA Institut, 2020)
The use of computer technology has been proven to help humans in various fields and aspects of life, including its use in the field of data management. The compilation of a computer technology-based asset data collection system application program design is expected to be able to help in the accuracy and speed of recording the utilization of data collection assets to see the wide coverage area under the supervision of the UPT. The exploitation of Aceh's Assets PT. Indonesian Railways (PERSERO). The general objective of this research is to design and build a more accurate asset database using the asset application system using Visual BASIC.NET and be able to know the usage of the asset application system that has been created and can present the asset application system that has been built at the UPT. The exploitation of Aceh's Assets so that the data collection system is more effective and efficient. The test results of this application are the systems that are built already meet the needs, the input data process has met the needs and the resulting report has met the needs.Keywords:Application Systems, Data Collection, Assets, UPT. Exploitation of Aceh's Assets PT. Kereta Api Indonesia (PERSERO), Visual Basic.NET.